The Legacy of Colonial Legal Politics on Islamic Law and Indonesian Adat Law: An Analysis of Snouck Hurgronje’s Thought - Sulaiman Kurdi; Ichwan Ahnaz Alamudi; Muhammad Torieq Abdillah; Husna Sari; Rena Zulfaidah (Syura: Journal of Law, 2026)
This research aims to analyze the political legacy of Dutch colonial law on Islamic law and adat law in Indonesia through a study of Christiaan Snouck Hurgronje’s thoughts. Different from previous studies that generally address colonial policy history, modern legislative convergence, or pre-colonial history in isolation, this study reconstructs Hurgronje’s receptie theory as a systematic instrument of legal engineering. This normative legal research employs historical and conceptual approaches by analyzing primary colonial documents as well as contemporary literature. The results demonstrate that prior to colonial intervention, Islamic law operated as an autonomous and sovereign legal system alongside customary law. Driven by Hurgronje’s doctrine that separated ritual Islam from political Islam, colonial policy systematically subordinated Islamic law to customary law (adatrechtpolitiek) through processes of dehistoricization and institutional marginalization. The findings affirm that this colonial legal engineering transformed an authentic and egalitarian pre-colonial legal pluralism into a hegemonical and segregative post-colonial legal system. Therefore, this study underscores the importance of deconstructing colonial epistemic biases to establish a fair and equal framework for national legal pluralism in Indonesia.